The Influence of Quality of Work Life, Mental Workload, and Self-Efficacy on Job Performance Mediated by Job Satisfaction in Nurses at Panglima Besar Soedirman Hospital - Marlin Feriani Sormin; Oscar Jayanagara (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
Nurses have a very important role in patient care in hospitals, namely integrated and quality nursing care for each patient. One of the most important things in Human Resources management is the performance of nurses. This study aims to analyze the direct influence of quality of work life, mental workload and self-efficacy on nurse performance, as well as the indirect influence of quality of work life, mental workload on nurse performance which is mediated by nurse job satisfaction at the Panglima Besar Soedirman National Defense Central Hospital, Jakarta. This research design is quantitative. Data collection used a non-probability sampling technique with a purposive sampling method. The sample used was 160 active nurses. This research data was collected using a questionnaire via Googleform. The data obtained was processed using the PLS-SEM multivariate analysis method with SmartPLS software. The results showed that quality of work life, mental workload and self-efficacy had a positive effect on nurses' job satisfaction. The results show that there is a positive influence on the quality of work life on nurse performance, then job satisfaction has a positive influence on nurse performance, but mental workload has a negative influence on nurse performance. The research results also show that self-efficacy has no effect on nurse performance. Quality of work life, mental workload and self-efficacy have an indirect influence on nurse performance through nurse job satisfaction. It is hoped that future research can conduct comparative studies between the health sector and other sectors to compare how factors such as quality of work life, mental workload, and self-efficacy influence job satisfaction and job performance.